Pemuda dan Wirausaha Pertanian: Hubungan Umur, Tingkat Pendidikan, Jenis Kelamin, Riwayat Keluarga Petani dengan Minat - Arum Pratiwi, Moerindra Sekar; Sugihardjo; Anantanyu, Sapja (Balai Pelatihan Pertanian Jambi, 2024)
The agricultural sector is the majority livelihood sector owned by the Indonesian population. Over time, Indonesia's agricultural development has been increasingly developed, this is evidenced by BPS data regarding the percentage of agricultural informal workers which increased in 2019 - 2021. The agricultural sector in Indonesia is currently experiencing the phenomenon of aging farmers, where there is a scarcity of youth who focus on working or working directly in the agricultural sector. The purpose of this study was to determine the bivariate relationship between age, education level, gender, and family history of farmers with youth interest in entrepreneurship in the agricultural sector. This research will be carried out in July-September 2023 in Wonogiri District, Wonogiri Regency. The research method used in this study is a quantitative research method using survey research techniques. The sample selection in this study used quota sampling and snowball sampling, with a research sample of 70 respondents, obtained by the Lameshow formula. The data analysis method in this study uses kai squared analysis, using SPSS 27. The results of this study are age, education level, and gender are not related to variables of interest in agricultural entrepreneurship, while farmer family history is related to youth interest in agricultural entrepreneurship.